Effect of aerobic fitness on the relation between age and whole‐body heat exchange during exercise‐heat stress: a retrospective analysis. Issue 9 (15th July 2020) - Notley, Sean R.; Meade, Robert D.; Kenny, Glen P.
Abstract : New Findings: What is the central question of this study? Does higher aerobic fitness, indexed by peak oxygen uptake ( V ̇ O 2 peak ), attenuate the age‐related decline in thermoregulatory function during exercise in the heat? What is the main finding and its importance? When assessed in aerobically fit and less fit adults ( V ̇ O 2 peak : ∼30 vs . ∼50 ml kg −1 min −1 ) aged 18–66 years, a steeper decline in whole‐body total heat loss (evaporative + dry heat exchange) was observed with increasing age in less aerobically fit adults. These outcomes indicate that increased aerobic fitness may attenuate the age‐related decline in thermoregulatory function during exercise‐heat stress. Abstract: Ageing is associated with decrements in cutaneous vasodilatation and sweating that attenuate whole‐body total heat loss (evaporative + dry heat exchange) during exercise‐heat stress. However, it remains uncertain whether increased aerobic fitness, as indexed by peak oxygen uptake ( V ̇ O 2 peak ), slows that age‐related decline. To evaluate this possibility, we conducted a retrospective analysis of data from aerobically fit ( n = 38; V ̇ O 2 peak : (mean (SD)) 49 (4) ml kg −1 min −1 ) and less fit ( n = 35; V ̇ O 2 peak : 32 (3) ml kg −1 min −1 ) adults spanning a broad age range (18–65 vs . 18–66 years). Participants performed three, 30 min bouts of cycling at metabolic heat productions of 150, 200 and 250 W m −2, each separated by 15 min recovery, in dry heat (40˚C, ∼15% relative humidity). Metabolic heat production and whole‐body total heat loss were measured using indirect and direct calorimetry, respectively. Total heat loss (mean (95% CI)) declined at a rate of 5 (2, 8), 6 (3, 8) and 5 (3, 10) W m −2 per decade during exercise at metabolic heat productions of 150, 200 and 250 W m −2, respectively, in less aerobically fit individuals (all P ≤ 0.002), due primarily to reductions in evaporative heat loss. In contrast, no significant associations between age and total heat loss were observed in aerobically fit individuals (all P ≥ 0.146). As such, the slope of the age‐related reduction in total heat loss was steeper in less fit compared to fit individuals across all three exercise bouts (all P ≤ 0.029). These outcomes indicate that increased aerobic fitness attenuates the age‐related decline in exercise thermoregulation. Abstract :